1970
DOI: 10.3126/sw.v5i5.2653
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Aqueous Extract of Leaves of <i>Parthenium Hysterophorus</i> L. on Seed Germination and Seedling Growth of Some Cultivated and Wild Herbaceous Species

Abstract: Allelopathic effects of aqueous extract of leaves of Parthenium hysterophorus were studied on seed germination and seedling growth of three cereal crops (Oryza sativa L., Zea mays L. and Triticum aestivum L.), three cultivated crucifers (Raphanus sativus L., Brassica campestris L. and Brassica oleracea L.) and two wild species of family Asteraceae (Artemisia dubia Wall ex. Besser and Ageratina adenophora (Spreng) King and HE Robins). Seed germination of all crucifer species was completely inhibited at >2% leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
54
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 19 publications
13
54
0
2
Order By: Relevance
“…In most of the studies, its leaf and flower proved to be more phytotoxic than its stem and root (Wakjira et al, 2005;Marwat et al, 2008;Khan et al, 2012). Likewise, more inhibitory effects of these plant parts on root growth than shoot growth of maize, ryegrass, soybean and rice were also reported by Mersie & Singh (1987) and Maharjan et al (2007). In our study, the highest allelopathic activity of aqueous leaf extract of parthenium growing near the field border seem to be due to its higher total phenolic contents (6678.2 mg L -1 ), higher EC (9.89 dSm -1 ) and lower osmotic potential (-0.36MPa) as well as complex interactions of a large number of phenolic compounds, namely gallic acid (7.5 mg L -1 ), caffeic acid (12.9 mg L -1 ), 4 hydroxy-3-methoxy benzoic acid (37.1 mg L -1 ) and p-coumaric acid (9.4 mg L -1 ) (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In most of the studies, its leaf and flower proved to be more phytotoxic than its stem and root (Wakjira et al, 2005;Marwat et al, 2008;Khan et al, 2012). Likewise, more inhibitory effects of these plant parts on root growth than shoot growth of maize, ryegrass, soybean and rice were also reported by Mersie & Singh (1987) and Maharjan et al (2007). In our study, the highest allelopathic activity of aqueous leaf extract of parthenium growing near the field border seem to be due to its higher total phenolic contents (6678.2 mg L -1 ), higher EC (9.89 dSm -1 ) and lower osmotic potential (-0.36MPa) as well as complex interactions of a large number of phenolic compounds, namely gallic acid (7.5 mg L -1 ), caffeic acid (12.9 mg L -1 ), 4 hydroxy-3-methoxy benzoic acid (37.1 mg L -1 ) and p-coumaric acid (9.4 mg L -1 ) (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 87%
“…The phytotoxic inhibition of germination and growth of maize and other crops by allelochemicals produced from various plant parts of parthenium have been well documented (Wakjira et al, 2005;Maharjan et al, 2007;Marwat et al, 2008;Dhole et al, 2011;Khan et al, 2012;Devi & Dutta, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Canola was more sensitive as compared to wheat crop. Maharjan et al (2007) have reported that inhibition in seed germination of the crucifer species (Raphanus sativus, Brassica campestris and B. oleracea) was more pronounced as compared to Oryza sativa, Triticum aestivum, Ageratina adenophora and Artemisia dubia even at a low concentration. It was noted that species varied considerably in their sensitivity to aqueous extracts of parthenium (Belz et al, 2007;Rashid et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous extract of jatropha leaf was prepared following the method given by Maharjan et al, (2007). Fresh jatropha leaves weighing 200 gm were ground homogeneously in a mortar and mixed with 1000 ml of distilled water and kept for 24 hours.…”
Section: Methodsmentioning
confidence: 99%